Adolescent Psychology and Their Problems in the Educational Process - Tolliboyeva , Charos; Davletmuratova , Maftuna; Adilova , Yulduzxon (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This article analyzes the psychological characteristics of adolescence and the problems that adolescents face in the educational process. Adolescence is one of the most complex and important stages of human development, during which a person’s worldview, interests, and social relationships are formed. The article highlights the psychological aspects of adolescents such as emotional changes, self-awareness, and the need for communication with peers. In addition, issues encountered in the educational process, including decreased learning motivation, lack of attention, reduced interest in studying, and difficulties in relationships with teachers and parents are examined. The study concludes that psychological support, individual approach, and the creation of a positive learning environment by teachers and parents play an important role in solving adolescents’ educational problems.